PENERAPAN DIGITAL TWIN UNTUK MENGURANGI DAMPAK BENCANA - Patandianan, Maraya Abisurya; Assidiq, Fuad Mahfud (Departemen Teknik Kelautan Fakultas Teknik Universitas Hasanuddin, 2022)
A country cannot avoid disasters, be it natural disasters or disasters caused by human carelessness. Disasters are increasing day by day. Damage and casualties are inevitable. In the industrial era 4.0, it is time to apply the latest technology to the focus of infrastructure, namely construction design and disaster prevention to reduce the amount of damage and casualties. Digital Twin (DT) is one of the promising technologies to conquer these challenges. The widespread use of Building Information Modeling (BIM) and the advent of the Internet of Things (IoT) apply DT to predict disasters by relying on historical data. This study proposes the use of DT technology due to the lack of reference, knowledge and application of this technology on real buildings or models to prevent and reduce the impact of disasters.